Color Categorization and its Electroencephalography Correlates: A Review of Neuro-Linguistic Oddball Paradigm Research - Yu. A. Griber (Научный диалог)
This paper presents a review of neuro-linguistic studies on color categorization, developed using the oddball paradigm. The selection of research sources was conducted through Russian National Corpus, Google Scholar, Scopus, Web of Science. This study undertook a comprehensive analysis of all relevant articles published within the last 15 years (with the earliest dating back to 2007). Through this analysis, traditional methodologies were identified and five thematic groups of research were established, all of which employed the oddball paradigm. The focus of neuro-linguistic research has been shown to be directed towards (1) studying the neurophysiological mechanisms of color categorization and their temporal parameters; (2) investigating the mechanisms of color categorization in preverbal infants; (3) examining the effect of lateralization; (4) analyzing inter- and intra-linguistic differences in color categorization; and (5) determining the neurophysiological correlates of artificial color categories. Paying particular attention to experimental design, principles of stimulus chromatic characteristics selection, and the results obtained by the authors will enable specialists in the field of theoretical, applied, and comparative linguistics to use the review presented in this article as a basis for planning and developing new experimental research in this area.